12.15 Variation in neurology training: experiences from sites across the UK. Issue 12 (14th November 2019) - Shribman, Samuel; Alexander, Sian; Zarkali, Angelika; Warner, Thomas T; Pereira, Anthony; Hughes, Tom; Mummery, Catherine J
Abstract : There is little evidence-based consensus on how to approach, structure or deliver neurology training. The General Medical Council conducts a National Trainee Survey in the UK on an annual basis and, while the results suggest significant variation in the quality of neurology training, they do not provide an explanation for this variation. In order to better understand how to train a neurologist we used the National Trainee Survey to identify four of the highest and lowest performing sites for neurology training across the UK and visited them to conduct semi-structured interviews with groups of trainees and, separately, local trainers. We identified common themes between the two groups of sites across a range of different aspects of neurology training. These included supervision, competency-based training, clinic attendance, subspecialty exposure, local teaching programmes and the educational culture within departments. Here, we present our findings, including case studies from top performing sites, and provide recommendations with specific examples for how to train a neurologist.